Electronic Health Records in Danish Home Care and Nursing Homes: Inadequate Documentation of Care, Medication, and Consent - Hertzum, Morten (Applied Clinical Informatics, 2021)
Background Electronic health records (EHRs) are used in long-term care to document the patients' condition, medication, and care, thereby supporting communication among caregivers and counteracting adverse drug events. However, the use of EHRs in long-term care has lagged behind EHR use in hospitals. In addition, most EHR research focuses on hospitals.Objective This study gives a countrywide status of the documentation-related risks to patient safety in Danish home care and nursing homes, which are the two main providers of long-term care. Such a status provides a basis for national improvement efforts and international comparisons.Method The study is based on the reports from 893 inspections of home care and nursing homes by the Danish Patient Safety Authority (Styrelsen for Patientsikkerhed [STPS]).Results As much as 69% of the inspected institutions document inadequately to an extent that has led to demands (i.e., issues the institution is legally obliged to rectify) or requests (i.e., issues the institution is merely asked to rectify) from STPS. Documentation issues about the patients' condition and care are present in nearly all institutions that receive demands (97%) and in the majority of those that receive requests (68%). Documentation issues about medication and consent to care are also common, but less so. The predominant risk to patient safety is incomplete documentation. It covers 72% of the documentation issues identified in the institutions that received demands; the remaining risks concern inconsistent (11%), nonexistent (7%), inaccessible (5%), and noncompliant (5%) documentation. The documentation inadequacies are similar for home care and nursing homes.Conclusion Inadequate EHR documentation is a widespread problem in Danish long-term care. While previous research mainly focuses on how EHR documentation affects patient medication, this study finds that documentation issues about the patients' condition and care are more prevalent and that issues about their consent are also common.
Keywords: electronic health record; patient-safety risk; long-term care; home care; nursing home